2012
DOI: 10.1002/anie.201200761
|View full text |Cite
|
Sign up to set email alerts
|

6′′‐Thioether Tobramycin Analogues: Towards Selective Targeting of Bacterial Membranes

Abstract: Amphiphilic tobramycin analogues with potent antibacterial activity against tobramycin‐resistant bacteria were synthesized. Most analogues were found to be less prone to deactivation by aminoglycoside‐modifying enzymes than tobramycin. These compounds target the bacterial membrane rather than the ribosome (see picture). The lipophilic residue of these analogues is key to their antibacterial potency and selectivity towards bacterial membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
120
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 32 publications
4
120
0
Order By: Relevance
“…In recent years, several studies have demonstrated the potential of exploiting aminoglycosides for the development of new cationic amphiphilic antimicrobial agents by converting part or all of their amine and hydroxyl functions into alkyl-or aryl-amide and ether groups, respectively (19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…In recent years, several studies have demonstrated the potential of exploiting aminoglycosides for the development of new cationic amphiphilic antimicrobial agents by converting part or all of their amine and hydroxyl functions into alkyl-or aryl-amide and ether groups, respectively (19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…From in-vitro inhibition test of the antibiotic kanamycin of phage R17 RNA, it was found that kanamycin B has a stronger activity than kanamycin A, while kanamycin C has the weakest activity compared to both kanamycin A and B [28][29]. More researches have been devoted to chemical modification of aminoglycoside antibiotics such as kanamycin with the goal of increasing antibacterial activities or new activities as antibacterial [30][31][32][33]. Tc-kanamycin labeling studies have been carried out in the previous research by the indirect method using pyrophosphate as a co-ligand with the result of labeling efficiency of above 95% [34][35][36].…”
mentioning
confidence: 99%
“…[13] Many of these compounds exhibited bacteriolytic activity, raising the possibility that the mode of action in these cases involves membrane disruption rather than translation inhibition. Herein, we present the synthesis of 18 additional TOB variants (Scheme 1), establish their antibacterial activity profile, and investigate the mechanism by which the 18 novel and the 19 previously reported 6″-thioether TOB variants inhibit bacterial growth, using AG-resistant ribosomes with mutations in the primary helix h44 site.…”
mentioning
confidence: 99%
“…While compounds 3a – j , l , m , p – t , jj , and kk have been described previously, [1314] compounds 3k , n , o , and u – ii are new. Our collection encompasses a diverse set of 6″-substituents, including linear, branched, and cyclic alkyl groups, and substituted aromatic rings.…”
mentioning
confidence: 99%
See 1 more Smart Citation